Controllable fabrication of metal-confined carbon nanotubes from the self-templated conversion of supramolecular gel nanofibers. (June 2022) - Liu, J.; Gu, C.; Wang, M.; Cui, Y.; Li, J.; Liu, C.-S.
Abstract: Nanostructured supramolecular gels with self-assembled fibrillar networks are promising candidates for fabricating advanced functional materials for energy-related applications. Several fundamental challenges, including poor structural stability and monotonous fibrous morphology, greatly hinder their practical applications. To the best of our knowledge, supramolecular gel-derived carbon nanotubes (CNTs) have not been reported in the literature. Herein, we present a unique strategy for controllable fabrication of metal-confined carbon nanotubes (M/CNT) from the self-templated conversion of guanosine-based supramolecular gel (GSMG) nanofibers. Benefitting from the high tunability of GSMGs, it was demonstrated that the introduction of metal source (Ni and Fe) to improve the stability of the material and simply changing the KOH concentrations in the precursor materials, the structure of GSMG nanofibers derived active materials was controllably tuned from metal-constrained solid carbon nanofiber to hollow M/CNT. The optimized NiFe/B, N-CNT showed a superior oxygen evolution reaction catalytic activity with a low overpotential of 355 mV at a current density of 10 mA cm −2 . By taking advantage of the unique structural features of supramolecular gels, this strategy provides a simple and effective synthetic route for functional CNT. Graphical abstract: A controllable preparation strategy for supramolecular gel-derived carbon nanotubes was firstly developed, in which the derived materials can be effectively adjusted from solid M/CNF to hollow M/CNT and used as highly efficient OER electrocatalysts. Image 1 Highlights: Controllable fabrication of supramolecular gel-derived carbon nanotube (CNT) was first developed. The derived materials can be effectively tuned from solid M/carbon nanofiber to hollow M/CNT. The NiFe/B, N-CNT were explored as highly efficient electrocatalysts for oxygen evolution reaction.